Bioeconomy as a driver for upcoming 7th K-wave (2050-2100) - Wilenius Markku (Springer, 2022)
This chapter sets out to project the future role of bioeconomy in our socio-economic structure in the light of the so-called Kondratieff long-wave theory. This framework presupposes 40–60 year-long economic cycles, and according to the author’s interpretation of the theory, we are now embarking into the sixth wave (2010–2050), followed by the seventh wave 2050–2100. This chapter sets out to understand the development of the waves in the light of the changing relationship of humans with nature. The assumption is that as we move towards mid-century, our relationship with nature will turn into a more collaborative form, away from the extractive practice of current economies. This chapter explores four potential domains for bioeconomy development in this respect: (1) agriculture, turning to more regenerative and becoming a part of the solution to climate problem; (2) forestry, expanding its role as a source of new materials, medicine and well-being; (3) algae production, becoming an essential source of energy and new materials production; and (4) biomimicry, being extensively deployed as a design principle for emerging technologies. All this potential development will signify exponential growth of the impact of bioeconomy for our societies to come.
Bio#Futures: Foreseeing and Exploring the Bioeconomy